Design of the water strider-like robot - Yatsyshyn, Svyatoslav; Zeng, Xinyu (Видавництво Львівської політехніки, 2023)
The development of the human population produces ecosystem changes. Monitoring of them can be considered one of the key prerequisites for ensuring its survival. At the same time, the development of Metrology 4.0 based on the study of land massifs and the control of their characteristics should consider the methods and means for studying the aquatic environment by new types of robots, as platforms for deployment of some sensors, namely multi-legged walking devices, for example, the “water striders”. In the paper, we consider the possibility of solving the quite complex task of designing of light robot designed to slide on the surface of the water without submerging in it and equipped with built-in sensors.
Keywords: Light robot; Design of water strider-like robot; Hardware; Software